Craig Hill. Teaching Comics Through Multiple Lenses: Critical Perspectives. New York: Routledge, 2017. - Jacinta Yanders (Studies in 20th & 21st Century Literature, 2017)
Review of Craig Hill. Teaching Comics Through Multiple Lenses: Critical Perspectives. New York: Routledge, 2017.
Keywords: Teaching comics; pedagogy studies; pop culture; reading communities